PEMBUATAN PLANG PEMBATAS JALAN ANTAR DUSUN SEBAGAI UPAYA PEMBERI INFORMASI DI DESA PEMATANG PANJANG KECAMATAN AIR PUTIH KABUPATEN BATU BARA - Nasution, Suhela Putri; Hasibuan, Abdurrozzaq; Napid, Suhardi; Ananda, Rizki; Azhari, Faisal (Universitas Islam Sumatear Utara, 2024)
Roads in several villages have major problems, namely damage that occurs at several points on the road and the absence of road signs. This problem also occurs in Pematang Panjang Village, Air Putih District, Batubara Regency. To overcome this problem and facilitate road access to the hamlets in Pematang Panjang Village, the Community Service Team has carried out activities to provide road signs for local hamlets to facilitate and complete the infrastructure for directional guidance to the hamlets. The activity is carried out in 4 (four) activity stages, namely: 1. Firstly carrying out a field survey at the location which will later become the installation point for the village road sign, 2. Preparing tools and materials to make the village road sign, 3. Carrying out the painting process and 4. Installation of village road signs by students assisted by youth and local communities. There are 13 signs with the name of the hamlet. This program received support and assistance from the youth and community of PematangGanjang Village so that it could be implemented well. In the process of activities from preparation to program implementation, no significant obstacles were found.